THE EFFECT OF PERSONAL EXPERIENCE STRATEGY ON STUDENTS’ ACHIEVEMENT - Juwita Hairani; Muhammad Sahid (BRIGHT VISION Journal of Language and Education, 2023)
The main topic of this study is teaching narrative text. The aim of this study is to seek out writing narrative text’s effect between the scholars taught by using personal experience strategy and therefore the students taught by using big group work strategy at tenth grade students’ of SMA Negeri 1 Pangkalan Susu. The experimental class was using personal experience strategy and therefore the controlled class was using big group work strategy. The author used quantitative method and also the research design  was experimental design.  In conducting  this  research, the population  was  tenth  grade and  brought  by sampling technique. The instrument in conducting the information during this study was essay test. There have been 500 scores gained of the pre-test to the post-test experimental class and there have been 211 scores gained of the pre-test to the post-test in controlled class. The finding showed that t-observed = 6.738 was on top of t-table = 1.667 at the amount of significance ∝ = 0.05 and therefore the degree of freedom (df) = 68. So, the null hypothesis (H0) was rejected and alternative hypothesis (Ha) was accepted, because t-observed  was  more  than  t-table  (t0  >  t  table  =  6.738  >  1.667).  Lastly,  personal experience strategy affected students’ achievement in writing narrative text.